Application of Psychoreligious Therapy: Dhikr in Mental Health Nursing Care for Auditory Hallucination Patients - Yudistira Afconneri; Gayatri Putri; Renidayati Renidayati; Surya Effendi (Journal of Applied Holistic Nursing Science, 2026)
Background: Mental disorders are maladaptive responses to internal and external stressors that lead to changes in patterns of thinking, perception, behavior, and emotions. Schizophrenia, as a severe mental disorder, is often characterized by an inability to distinguish between reality and illusion, one manifestation of which is auditory hallucinations that affect an individual’s thought processes; therefore, non-pharmacological management such as dhikr therapy is required. This study aimed to apply dhikr therapy as an intervention in mental health nursing care for patients experiencing auditory hallucinations in the Flamboyan Ward of Prof. HB Saanin Mental Hospital, Padang. Methods: The study employed a case report design involving two participants over a five-day nursing care period, following the stages of the nursing process including assessment, diagnosis, intervention, implementation, and evaluation, which were analyzed by comparing theoretical frameworks and previous studies. Results: The results showed a reduction in the severity of auditory hallucinations from a moderate to a mild level, indicated by a decrease in the hallucination score of patient FT from 20 to 9 and patient FF from 22 to 10. Conclusion: Therefore, this study is expected to serve as a reference for nurses in implementing generalist nursing interventions combined with dhikr therapy and to provide a basis for future researchers to use daily pre–post measurements throughout the intervention period.